The Wiener-Hopf method in electromagnetics - Zich, Rodolfo, 1939- (SciTech Publishing Inc., 2014)
This monograph presents the Wiener-Hopf method in theoretical electromagnetism.
Keywords: Wiener-Hopf equations.; Electromagnetism -- Mathematics.; Integral equations.; elektronické knihy; electronic books